Evaluation of the Effect of Glass-Fiber Post Length on Fracture Resistance of Endodontically Treated Central Incisors - Zafar Mahdavi Izadi; Ezatollah Jalalian; Mohammad hasan Salari; Goldis Khalili Shorini; Tahmineh Safaei; Shima Azimzad; Mohammad javad Kharazi Fard (Islamic Dental Association of Iran, 2013)
Background and Aim : Use of glass fiber posts is of widespread acceptance in restoring root canal treated teeth, but studies concerning the most proper length of the post to provide the utmost fracture resistance are inadequate. The aim of this study was to evaluate the effect of glass fiber post length on fracture resistance of root canal treated central incisors .   Materials and Methods : This experimental study was carried out on 40 maxillary central incisors in 4 groups of 10 each. RDT posts and cement was used in this experimental study with the lengths of 6, 8, 10, and 12 mm in the study groups. The samples were debrided and decoronated at the CEJ levels and endodontically treated using step-back technique. RDT drills were used for post space preparation. Then, the root canal walls were etched and the posts cemented in place. The composite cores were then prepared at the height of 5 mm and samples mounted 2mm down to their CEJ levels within acrylic blocks. An impression material (Impregum, 3M, ESPE) with a thickness of 0.2mm was used to simulate PDL around the samples. The samples were subjected to compressive forces at a 135-degree angle to their long axes using a Universal Testing Machine. Data pertaining to the fracture of the samples were analyzed using ANOVA and Tukey statistical tests .   Results : The maximum resistance to fracture was recorded in 8-and 10-mm-long posts and the minimum was observed in the lengths of 6 and 12 mm. Statistical tests showed a significant difference between 8- and 10-mm-long posts with those having lengths of 6 and 12 mm in terms of fracture resistance. There was no significant difference between 8- and 10-mm-long posts as well as 6- and 12-mm-long ones.   Conclusion: It can be concluded that the length of post is influential in the fracture resistance of the root so that the maximal resistance can be obtained in 8 to 10 mm of length and such lengths can be recommended for non-metal posts .